ANALISIS DAMPAK ADANYA EKOWISATA MANGROVE PADA KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI DESA PASIR KABUPATEN MEMPAWAH - Gita Ramadhani; Yohanes Bahari; Izhar Salim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
Ecotourism is an alternative form of tourism, which is formed as a reaction to various negative impacts of traditional tourism by making a trip to a natural or conservation area that supports environmental sustainability. Development of mangrove ecotourism is very important for humans and mangrove forests itself to prevent the damage of coastal areas. With the existence of ecotourism, it is expected to encourage the development and preservation of mangrove forests that have high value. The development of the ecotourism along with the local community can develop tourism objects while preserving mangrove forests. Mempawah Mangrove Park (MMP) is a tourist site for mangrove forests in Desa Pasir, Kecamatan Mempawah Hilir, Kabupaten Mempawah.This study aims to determine the impact of mangrove ecotourism on the socio-economic aspect of Desa Pasir Mempawah Hilir society. The method that will be used in this research is descriptive. Data collection techniques that will be used are observation, interview, and documentation. The data collection tools that will be used in this research are the observation guide, interview guide, and documentation. Data analysis will be data reduction, data display, and verification.